Die proses van partikuliere en openbare besluitneming - S. S. Brand (South African Journal of Business Management, 1983)
– Private and public decision-making The interaction between the private and public sectors is important in South Africa. Much criticism is expressed by the one sector against the other. This can be partly attributed to an incomplete understanding of the processes of decision-making in the two sectors, and of the differences between them. A comparison is drawn between the most important elements of the decision-making processes in the two sectors. Public decision-making deals mostly with matters concerning the community and the economy as a whole, whereas private decision-making is concerned mostly with parts of the whole. The aims at which decision-making in the two sectors are directed, differ accordingly, as do the perceptions of the respective decision-makers of the environment in which they make decisions. As a consequence, the criteria for the success of a decision also differ substantially between the two sectors. The implications of these differences between private and public decision-making for the approach to inflation and the financing of housing, are dealt with as examples. Finally, differences between the ways in which decisions are implemented in the two sectors, also appear to be an important cause of much of the criticism from the private sector about decision-making in the public sector.
Keywords: 650